2020
DOI: 10.1016/j.heliyon.2020.e04828
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of tides in the Malacca Strait with a 3-D model

Abstract: Malacca Strait (MS) has an important role and potential for many countries. It is a major transportation route for oil and commodities across continents. In addition, various activities such as shipping, fishing, aquaculture, oil drilling, and energy are also carried out in MS. Tides strongly affect the MS environment so that it becomes a major parameter in MS management. This paper is the first study, which presents MS tidal hydrodynamics based on a baroclinic and nonhydrostatic approach. Tidal hydrodynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
(62 reference statements)
1
15
0
4
Order By: Relevance
“…Our estimation of genetic connectivity among A. marina populations along the West coast of Malay Peninsula through comparison of migration models supported a putative unidirectional dispersal route that was congruent with prevailing ocean currents (Rizal et al, 2010(Rizal et al, , 2012Haditiar et al, 2020). This further emphasizes the relevance of coastal connectivity to mangrove persistence (Van der Stocken et al, 2019a,b) as well as the importance of apparently discrete estuaries.…”
Section: Connectivity Along Same Coastlinesupporting
confidence: 69%
“…Our estimation of genetic connectivity among A. marina populations along the West coast of Malay Peninsula through comparison of migration models supported a putative unidirectional dispersal route that was congruent with prevailing ocean currents (Rizal et al, 2010(Rizal et al, , 2012Haditiar et al, 2020). This further emphasizes the relevance of coastal connectivity to mangrove persistence (Van der Stocken et al, 2019a,b) as well as the importance of apparently discrete estuaries.…”
Section: Connectivity Along Same Coastlinesupporting
confidence: 69%
“…Furthermore, our demographic history analyses indicated that the Gulf populations of cryptic species B historically experienced a more recent expansion than Andaman Sea populations. Accordingly, we assume that the connectivity of B. tenella species B population across Thai-Malay Peninsula could possibly be associated with the historical subsidence of Sundaland, leading to a recent population expansion of this alga during the inundation of the Gulf of Thailand, and regional circulation patterns linking these two coastal areas (Haditiar et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The bathymetric profile and tidal oscillation cause this. Recently, Haditiar et al (2020) reported another way of tidal propagation from the South China Sea (SCS). The tides from the Andaman Sea in the north and the tides from the SCS through Singapore Waters in the south of the Malacca Strait meet in the middle, resulting in a shoaling in the region.…”
Section: Tide and Tidal Currentmentioning
confidence: 99%